The development of a crack propagation model for railway wheels and rails. Issue 12 (12th May 2015) - Dirks, B.; Enblom, R.; Ekberg, A.; Berg, M.
Abstract: Rolling contact fatigue (RCF) and wear of railway wheels and rails are the main phenomena that affect their maintenance costs. When crack propagation and wear rates can be predicted, maintenance planning can be optimised, and cost‐effective measures can be developed. Several RCF models exist, but none which can be used in combination with vehicle dynamics simulations and can predict the actual crack depth. This study shows the development of a crack propagation model that can be applied for both railway wheels and rails. Two unknown material parameters in the model were calibrated against crack measurements in a curve on the Dutch railways over a period of 5 years. Two different RCF models were used to calculate the stress magnitudes for the propagation model. The propagation model can be used in combination with vehicle‐track dynamics simulations and shows promise in predicting the actual crack depth and/or surface length. Further research is needed to determine the model's validity for other operational conditions.